Direct conversion of carbon dioxide to liquid fuels and synthetic natural gas using renewable power: Techno-economic analysis. (December 2019) - Zhang, Chundong; Gao, Ruxing; Jun, Ki-Won; Kim, Seok Ki; Hwang, Sun-Mi; Park, Hae-Gu; Guan, Guofeng
Highlights: Two options for direct conversion of CO2 to liquid fuels and synthetic natural gas are proposed. CO2 is converted via Fe-based F-T synthesis and CO2 methanation technologies. Process modeling and conceptual design are implemented using Aspen Plus. Techno-economic analysis is performed to evaluate the economic performance. Both options can be regarded as candidate technologies for direct CO2 conversion. Abstract: The conceptual design of a base case power-to-liquids (PTL) process that converts CO2 to liquid fuels and a hybrid PTL/power-to-gas (PTG) process that converts CO2 to liquid fuels and high-calorie synthetic natural gas (SNG) was carried out by using an Aspen Plus simulator. Based on the established process models, we conducted a technical study to investigate the effects of recycle ratios on the process performance such as the energy efficiency and the net CO2 reduction of the proposed hybrid PTL/PTG process, and compared it with the base case PTL process. After the technical study, an economic analysis was further implemented to evaluate the economic performance of the hybrid PTL/PTG and the base case PTL processes and to pursue the optimum process configuration of the proposed hybrid PTL/PTG process. According to the results of the technical study and economic analysis, it can be concluded that both the base case PTL process and the hybrid PTL/PTG process can be regarded as candidate technologies for the conversion of CO2 to value-added liquid fuels and/or high-calorie SNG. Moreover, the hybrid PTL/PTG process seems to be more efficient and profitable in utilizing CO2 because of its higher energy efficiency and net CO2 reduction as well as lower CO2 reduction cost in comparison with the base case PTL process.